FAM20A Mutations Associated with Enamel Renal Syndrome. (January 2014) - Wang, S.K.; Reid, B.M.; Dugan, S.L.; Roggenbuck, J.A.; Read, L.; Aref, P.; Taheri, A.P.H.; Yeganeh, M.Z.; Simmer, J.P.; Hu, J.C.-C.
We identified two families with an autosomal-recessive disorder manifested by severe enamel hypoplasia, delayed and failed tooth eruption, misshapen teeth, intrapulpal calcifications, and localized gingival hyperplasia. Genetic analyses identified novel FAM20A mutations associated with the disease phenotype in both families. The proband of Family 1 had an altered splice junction in Intron 1 (g.502011G>C; c.405-1G>C) and a missense mutation in Exon 8 (g.65094G>A; c.1207G>A; p.D403N). The missense mutation is notable because D 403 is strictly conserved among FAM20A homologues, and the corresponding defect in FAM20C caused osteosclerotic bone dysplasia and a loss of kinase activity. The proband at age 12 yrs tested negative for nephrocalcinosis. The proband and her affected father in Family 2 were homozygous for a single nucleotide deletion that altered a splice junction in Intron 10 (g.66622del; c.1361+4del). Minigene analyses demonstrated that this alteration precluded normal splicing. Immunohistochemistry (IHC) of mouse maxillary first molars localized FAM20A in secretory-stage ameloblasts, in odontoblasts, and in the eruption pathway. IHC of kidneys localized FAM20A in the renal tubules. We conclude that FAM20A is likely a secretory pathway kinase and that loss-of-function mutations cause pathology where its phosphorylations are necessary for normal development or homeostasis.